2023
DOI: 10.3390/s23115178
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Specific Strength Test in Handball Performance: Exploring Differences across Competitive Levels and Age Groups

Luis J. Chirosa-Ríos,
Ignacio J. Chirosa-Ríos,
Isidoro Martínez-Marín
et al.

Abstract: The aim of this study was to determine if specific physical tests are sufficiently discriminant to differentiate players of similar anthropometric characteristics, but of different playing levels. Physical tests were conducted analyzing specific strength, throwing velocity, and running speed tests. Thirty-six male junior handball players (n = 36; age 19.7 ± 1.8 years; 185.6 ± 6.9 cm; 83.1 ± 10.3 kg; 10.6 ± 3.2 years of experience) from two different levels of competition participated in the study: NT = 18 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…It is widely reported that anthropometry is an important variable for optim mance in team handball. Moreover, anthropometry is known to differ between play [37]. Although certain characteristics, such as total body mass, may be be some playing positions in handball, it may only be advantageous in one positi displayed the lowest body mass and Pivots were the players with the largest a body fat.…”
Section: Anthropometric Datamentioning
confidence: 99%
“…It is widely reported that anthropometry is an important variable for optim mance in team handball. Moreover, anthropometry is known to differ between play [37]. Although certain characteristics, such as total body mass, may be be some playing positions in handball, it may only be advantageous in one positi displayed the lowest body mass and Pivots were the players with the largest a body fat.…”
Section: Anthropometric Datamentioning
confidence: 99%
“…This study aimed to investigate how pain in various body parts affects subjective and objective handball performance during an actual training camp of a Japanese male national team. In general, a national team consists of a few selected elite players [ 15 ]. In addition, these athletes train at high intensity and prepare for international matches within a short preparation period, making it extremely difficult to establish a long and stable survey period.…”
Section: Introductionmentioning
confidence: 99%
“…Equipment reliability testing is necessary due to the increasing popularity of isometric testing as a means of determining maximum strength and the ability to apply peak force in the shortest possible time [10]. It is crucial to employ evaluations that can distinguish between different types of analytical advancements in force creation when measuring force [11]. When it comes to training and assessing the kinetic variables of power, speed, and strength of various human movements [12], as well as the various forms of muscular contraction and strength manifestations in free, mono-, or multi-joint movement of the entire body [13], functional electromechanical dynamometry (FEMD) is a perfect tool.…”
Section: Introductionmentioning
confidence: 99%